Pengaruh Disiplin Kerja, Motivasi Kerja dan Kesejahteraan Karyawan terhadap Produktivitas Karyawan melalui Kepuasan sebagai Variabel Intervening pada PT. J&T Express Cabang Surabaya - Nevityanda, Dinda; Ubaidillah, Hasan (Innovative Technologica: Methodical Research Journal, 2024)
This study aims to determine the effect of work discipline, wprk motivation, adn employee welfare on employee productivity through job satisfaction as an intervening variable at PT. J&T EXPRESS Surabaya Branch. This research is a descriptive study using quantitative methods. The data collection technique is by distributing questuonnaires to 80 respondents who are employee of PT. J&T Express. The analytical technique used in this research is multiple linear regression using SPSS (Statistical Program of Social Science). This results of this study incicate that work discipline affects employee productivity, work motivatuon affects employee productivity, employee welfare affect employee productivity, work discipline does not affect work goals, work motivation affects work goals, employee welfare affects productivity employee.